The Circuitous Nature of Operation Ajax - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
In seeking to protect its economic interests and its control of oil resources in Iran, Britain planned to overthrow Iranian Prime Minister Dr Mohammad Mossadegh in a military coup d'etat following his decision to nationalize the Iranian oil industry in 1951. However, the British initially faced strong opposition to this plan from the US under the Truman administration, which preferred a more diplomatic approach to the crisis and did not see British interests as being in line with its own. Facing this opposition and after unsuccessful attempts to oust the Iranian leader through economic pressure and propaganda campaigns, the British skillfully leveraged American fear of Communism to secure Washington, under the Eisenhower Administration, as a partner to lead a joint US-UK mission to overthrow Mossadegh. This paper explores the reasons behind the shift in American policy regarding this issue, exploring whether it was the Brit's successful use of covert, circuitous tactics to achieve their intended outcomes or solely a result of ideological differences between the two US administrations